Educational resource for antimicrobial resistance and stewardship for dentistry programmes: a research protocol - Long Chiau Ming; Muhammad Eid Akkawi; Chuan Yok Ang; Jagjit Singh Dhaliwal; Siti Hanna Muharram; Zahid Hussain; Hanif Rahman; Yuh Yen Kok; Sachinjeet Kaur Sodhi Dhaliwal (BMJ Open)
Introduction Antimicrobial resistance (AMR) is a global public and patient safety issue. With the high AMR risk, ensuring that the next generation of dentists that have optimal knowledge and confidence in the area of AMR is crucial. A systematic approach is vital to design an AMR content that is comprehensive and clinically relevant. The primary objective of this research study will be to implement a consensus-based approach to elucidate AMR content and curriculum priorities for professional dentistry programmes. This research aims to establish consensus along with eliciting opinion on appropriate AMR topics to be covered in the Bachelor of Dental Surgery syllabus.Methods and analysis A three-phase approach to validate content for curriculum guidelines on AMR will be adopted. First, literature review and content analysis were conducted to find out the available pertinent literature in dentistry programmes. A total of 23 potential literature have been chosen for inclusion within this study following literature review and analysis in phase 1. The materials found will be used to draft curriculum on antimicrobials for dentistry programmes. The next phase involves the validation of the drafted curriculum content by recruiting local and foreign experts via a survey questionnaire. Finally, Delphi technique will be conducted to obtain consensus on the important or controversial modifications to the revised curriculum.Ethics and dissemination An ethics application is currently under review with the Institute of Health Science Research Ethics Committee, Universiti Brunei Darussalam. All participants are required to provide a written consent form. Findings will be used to identify significant knowledge gaps on AMR aspect in a way that results in lasting change in clinical practice. Moreover, AMR content priorities related to dentistry clinical practice will be determined in order to develop need-based educational resource on microbes, hygiene and prudent antimicrobial use for dentistry programmes.